Group Exhibition-From the Chisel to the Electron. 50 Years of Cypriot Sculpture Kasteliotissa, Nicosia - Antoniou, Klitsa (My University, 2026)
From the Chisel to the Electron. 50 Years of Cypriot Sculpture Kasteliotissa, Nicosia, Cyprus